2017
DOI: 10.5195/cajgh.2017.244
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tobacco Smoking and Factors Associated with the Initiation of Smoking among University Students in Dhaka, Bangladesh

Abstract: Introuduction: Tobacco smoking is considered to be the key preventable risk factor for morbidity and mortality at the global level. The aim of this study was to determine the prevalence of tobacco smoking and factors associated with the initiation of smoking among university students in Dhaka, Bangladesh.Methods: A cross-sectional survey study was conducted with 264 students of Jahangirnagar University, Dhaka, Bangladesh in 2015. A standard, self-administered questionnaire consisting of questions on socio-demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 25 publications
6
64
1
1
Order By: Relevance
“…Peers of similar age or who are slightly older are strong influences on behaviors in youth, including health behaviors. There is considerable evidence that peers can influence the development of both risky health behaviors and positive health behaviors . The CST program was developed to be highly interactive, with role playing of common social situations.…”
Section: Discussionmentioning
confidence: 99%
“…Peers of similar age or who are slightly older are strong influences on behaviors in youth, including health behaviors. There is considerable evidence that peers can influence the development of both risky health behaviors and positive health behaviors . The CST program was developed to be highly interactive, with role playing of common social situations.…”
Section: Discussionmentioning
confidence: 99%
“…11 The percentage of current smokers among university students in Bangladesh was 60.2%. 12 In China, the prevalence of current smoking among male undergraduate's students was 91.8%. 13 The prevalence of current smoking among college students in USA was 42%.…”
Section: Discussionmentioning
confidence: 99%
“…Data on active smokers from the 2017 Global Adult Tobacco Survey (GATS) found that as many as 67% of men smoke, 2.7% of women smoke, 80.4% of the population who smoke currently smoking only clove cigarettes. Data from adolescent passive smokers shows that the prevalence of smoking in 2007 was 3 times in boys and 5 times in girls compared to 1995 (Hossain et al, 2017).…”
Section: Introductionmentioning
confidence: 96%